Anti-mycobacterial alkaloids, cyclic 3-alkyl pyridinium dimers, from the Indonesian marine sponge Haliclona sp. Issue 15 (1st August 2017) - Maarisit, Wilmar; Abdjul, Delfly B.; Yamazaki, Hiroyuki; Kato, Hajime; Rotinsulu, Henki; Wewengkang, Defny S.; Sumilat, Deiske A.; Kapojos, Magie M.; Ukai, Kazuyo; Namikoshi, Michio
Graphical abstract: Abstract: Three new dimeric 3-alkyl pyridinium alkaloids, named haliclocyclamines A–C (1 –3 ), were isolated together with five known congeners, cyclostellettamines A (4 ), B (5 ), C (6 ), E (7 ), and F (8 ), from the Indonesian marine sponge Haliclona sp. The structures of1 –3 were assigned based on their spectroscopic data (1D and 2D NMR, HRFABMS, ESIMS/MS, UV, and IR). Compounds1 –8 exhibited antimicrobial activities against Mycobacterium smegmatis with inhibition zones of 17, 10, 13, 14, 8, 8, 12, and 12 mm, respectively, at 10 μg/disc. Compounds3 and8 also modestly inhibited the activity of vaccinia H-1-related phosphatase (VHR), a dual-specificity phosphatase, at 17–18 μM.